Hinduism and the Global Village - Sundararajan, K R (Religious Studies and Theology, 2010)
As the world evolves into a “global village,” a community in which people of different religious persuasions, ethnic and cultural diversities functioning together with common goals is being formed. However, this movement stretches the theological and traditional resources of adherents of religions whose doctrines have hitherto been silent on “believers versus non-believers” or “insiders versus outsiders” relationships. Against this backdrop, this article examines the challenges that Hindus in diaspora-communities face, especially the inevitability of interacting with other members outside the Hindu faith. It is concluded that the notion of a “global village” presents an opportunity to explore the possible resources and dynamism of the Hindu tradition for a community living, where the community is constituted of members of diverse religious groups.